ORGANOLEPTIC CHARACTERISTIC OF BROWNIES FROM MOCAF AND GREEN BEAN FLOUR - Nezly Nurlia Putri; Nia Ariani Putri; Rahma Hariyanti (University of Sultan Ageng Tirtayasa, 2021)
The development of local food is one of the programs being promoted by the ministry of agriculture and as an effort to diversify food in the midst of the Covid-19 Pandemic. One of the local food commodities developed was cassava. Based on data from the Central Statistics Agency related to cassava productivity in Indonesia (2014 – 2018) it was in the range of 229.51 – 246.50 tons/year. the average percentage of flour consumption per capita from 2014 –2018 is 19.92%. In addition, the cassava industry had also begun to develop, namely the processing of cassava into Modified Cassava Flour (Mocaf). Organoleptically, the value of Mocaf (in terms of aroma and taste) was almost equivalent to wheat. One way to control the value of imported flour is by developing products based on local food ingredients. Based on this, local food preparations based on modified cassava flour were developed, namely mocaf and fortified green bean flour as a source of protein. Processed products from cassava and green bean are able to substitute the use of flour 10-100%. This study aims to determine the effect of MOCAF formulation and green bean flour on the organoleptic characteristics of brownies. The flour formulations used for the four treatments (MOCAF wheat flour and green bean flour) were based on the ratio of the composition of each flour. Furthermore, observations were made on the organoleptic characteristics of roasted brownies consisting of color, scent, texture, taste and after taste. Organoleptic test involved 30 untrained panelists using the hedonic method. Organoleptic test results illustrate that the overall product is acceptable, both in terms of taste, aroma, color, texture and after taste. In treatment A, which is brownies with a composition ratio of flour, mocaf and green bean flour (1:3:0), the panelists are generally preferable. In Treatment C, brownies with a composition ratio of flour, mocaf and green bean flour (1:2.33:0.75) only tasted better by the panelists. This indicates that the panelists prefer the addition of green bean flour less than mocaf.